How accurately do instructors judge students' attitudes online? A measurement of expectations and level of satisfaction with an Online Information Systems masters program - Lauren-Nicole Macht; Jenny Preece (Association for Learning Technology, 2002)
In order to run a successful educational program, instructors as well as staff members must constantly review and adapt to the expectations, concerns, demographics and satisfaction level of their student consumers. This study was conducted in order to examine these issues in an online educational setting. First, interviews were given to the program instructors in order to determine their opinions about the students' expectations and satisfaction levels. This information was then used to create a student survey that assessed the students' expectations and level of satisfaction. These two sets of results were then compared This comparison revealed that the online instructors did have a good grasp of the online students' expectations, concerns, demographics and satisfaction level. The only areas where the instructors' concepts of student views were slightly less accurate was student concerns and student feelings about the program administration, where the instructors overestimated the level of concern the students had about successfully returning to the learning environment and underestimated the students' satisfaction with the program's administration. This leads us to conclude that, even with the added online factor, instructors strongly understand student expectations, satisfaction levels, demographics and concerns.